Brake Rating Selection and Running-speed Limit Investigation of Freight Train - 曹兴贵 (机车电传动)
Based on calculation and analysis, the conditions of wheel keeping from sliding in brake, selection of freight train brake rating, and relations between train axle, the highest running speed, distance limit of emergency brake, and brake rating were expounded. It was pointed that the train highest running speed must be reduced when the axle load was increased to 25~30 t without extending brake distance limit, on the other hand, the train brake distance limit must be extending to keep the highest running speed.